Strategi Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Atas Kartika 1-2 Medan - Ismalia Putriana Br Simbolon; Nanda Rahayu Agustia; Abdi Syahrial Harahap (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2026)
This study examines the principal’s leadership strategies in improving the quality of Islamic Religious Education learning at Senior High School Kartika 1-2 Medan. The research addresses how school leadership contributes to strengthening instructional quality, teacher professionalism, learning facilities, and evaluation systems within Islamic Religious Education classes. This study employed a qualitative method with a case study approach, and data were collected through in-depth interviews with relevant informants involved in the learning process. The findings reveal that the principal implemented several strategic initiatives, including enhancing teacher professionalism through continuous guidance and supervision, improving learning facilities and infrastructure such as reference books and instructional media, encouraging interactive and student-centered learning activities, and establishing a structured evaluation system to monitor the effectiveness of Islamic Religious Education learning. The study also found that the leadership approach fostered a more conducive learning environment and strengthened student participation in religious activities. This study concludes that the principal’s leadership plays a significant role in improving the quality of Islamic Religious Education learning through adaptive management, continuous evaluation, and the integration of professional development and educational support systems.